Adaptive contour based printing of a propeller using hybrid-wire arc additive manufacturing. (2022) - Elkhouly, Youssef M; Lim, Wei Sheng; Dharmawan, Audelia Gumarus; Soh, Gim Song
Abstract: In this paper, we discuss our approach to printing a propeller blade using the hybrid wire arc additive manufacturing set up at the Singapore University of Technology and Design. This setup can perform both additive and subtractive processes within an integrated work cell. The propeller additive tool path planning is done using the adaptive level-set contour method. Together with a hybrid method, it enabled us to build a propeller with minimum material spillage and without the need to use overhang calculations, which shows the benefits of using both processes to overcome some limitations of WAAM printing. The same propeller was printed without using the hybrid method and compared to the hybrid one, the comparison shows the effect of the subtractive method -as the hybrid method- in printing consistently and more accurately.